How can operational oceanography products contribute to the European Marine Strategy Framework Directive? The Italian case. (12th February 2016) - Rinaldi, E.; Orasi, A.; Morucci, S.; Colella, S.; Inghilesi, R.; Bignami, F.; Santoleri, R.
ABSTRACT: Operational oceanography products have been used to define the Marine Strategy Framework Directive (MSFD) good environmental status (GES) relative to the Italian marine ecosystem subregions. Observations include sea surface temperature (SST), winds and chlorophyll Mediterranean Sea satellite products and Italian national tide gauge network winds. These were used to obtain SST seasonal climatology data and trends, 90th percentile of chlorophyll climatology data and SST and wind coastal upwelling indices. Also, Eulerian and Lagrangian circulation models have been used to map the residence time (RT) of Lagrangian particles in the marine subregions, which mimics pollutant dispersion capability at a given location and time.